Depressive symptoms and structural disease progression in knee osteoarthritis: data from the Osteoarthritis Initiative. Issue 1 (January 2017) - Rathbun, Alan; Yau, Michelle; Shardell, Michelle; Stuart, Elizabeth; Hochberg, Marc
Abstract Depressive symptoms are associated with increases in pain and functional limitations in knee osteoarthritis (OA). The aim was to determine whether depressive symptoms are also associated with greater structural knee OA progression. Four years of annual radiographic and clinical assessments from the Osteoarthritis Initiative were analyzed. The Center for Epidemiological Studies Depression Scale was used to identify depressive symptoms (threshold = ≥16) at the baseline visit. Propensity scores were used to match participants with and without baseline depressive symptoms on multiple potential confounders. Assessment of radiographic knee OA was based on changes in individual radiographic features, which included osteophyte (OST) grade and joint space narrowing (JSN) grade. Mixed effect models were used to examine structural progression between depressed and non-depressed participants with definitive radiographic knee OA. Depressive symptoms were significantly associated with a higher risk of OST progression (odds ratio [OR] = 1.74; 95% confidence interval [CI]: 1.01, 3.00) and a non-significant lower risk of JSN progression (OR = 0.40; 95% CI: 0.14, 1.15) 1 year after baseline. Conversely, there was a non-significant lower risk of OST progression (OR = 0.71; 95% CI: 0.28, 1.79) and higher risk of JSN progression (OR = 1.89; 95% CI: 0.71, 5.06) from year 3 to year 4 of follow-up. However, the patterns of OST progression and JSN progression were not significantly different between the depressed and non-depressed (P  = 0.25 and 0.15, respectively). The findings provide no evidence that depressive symptoms have a detectable effect on changes in radiographic disease severity in knee OA.